Faktor-Faktor Yang Memengaruhi Intellectual Capital Disclosure Pada Perusahaan Manufaktur - Cynthia Tatang; Sukrisno Agoes; Henny Wirianata (Jurnal Ekonomi, 2022)
The purpose of this research was to examine the effect of profitability, leverage, firm size, institutional ownership, and independent commissioner on intellectual capital disclosure in manufacturing companies listed on the Indonesia Stock Exchange in the period 2018-2020. This research used 68 manufacturing companies as samples after being selected by purposive sampling method. The data was processed using the EViews 12 SV program. The result of this research showed that firm size and institutional ownership had positive effect on intellectual capital disclosure, while profitability, leverage, and independent commissioner had no effect on intellectual capital disclosure.